Genomic and phenotypic characterization of Enterococcus faecalis from broiler sternal bursitis: antimicrobial resistance and one health risks - Jessica Ribeiro; Vanessa Silva; Pedro Pinto; Madalena Vieira-Pinto; Rita Batista; Alexandra Nunes; João Paulo Gomes; Gilberto Igrejas; Lillian Barros; Sandrina A. Heleno; Filipa S. Reis; Patrícia Poeta (Veterinary Research Communications, 2026)
Enterococcus spp. are opportunistic bacteria capable of acquiring antimicrobial resistance and virulence traits, facilitating their adaptation to multiple ecological niches. Sternal bursitis, a condition affecting poultry welfare and carcass quality, remains poorly characterized from a microbiological perspective. This study provides the first genomic and phenotypic characterization of Enterococcus isolates from bursitis lesions in broilers, aiming to assess their antimicrobial resistance profiles, virulence determinants, and genetic diversity within a One Health framework. A total of 44 Enterococcus isolates were recovered from 48 sternal bursitis lesions, all identified as E. faecalis . Resistance was common for tetracycline (70.5%) and erythromycin (27.3%), while all isolates remained susceptible to critically important antimicrobials, including vancomycin and linezolid. Whole-genome sequencing revealed a genetically diverse population, comprising multiple sequence types, plasmid replicons, and virulence gene profiles, including determinants for adhesion, biofilm formation, capsule synthesis, and extracellular proteases. Ionophore resistance genes ( narA , narB ) were also detected in several lineages. The coexistence of antimicrobial resistance and virulence determinants, often linked to mobile genetic elements, highlights the potential of lesion-associated with E. faecalis to act as reservoirs of relevant genes with zoonotic implications. Overall, this work highlights the diverse and ecological role of Enterococcus in extraintestinal poultry infections, reinforcing the need for continued genomic surveillance to promote animal health, food safety, and antimicrobial stewardship.

In vivo evaluation of the anti-inflammatory efficacy of liposomes loaded with Echinacea purpurea roots extracts - Sara F. Vieira; Diana Fonseca-Rodrigues; Daniel Mendanha; Vânia I. B. Castro; Ricardo A. Pires; Rui L. Reis; Filipa Pinto-Ribeiro; Helena Ferreira; Nuno M. Neves (Drug Delivery and Translational Research, 2026)
WHO ranked chronic inflammatory diseases as the most significant cause of death. The current therapeutic approach is the constant administration of clinically available anti-inflammatory drugs; however, this strategy presents severe side effects. New entities derived from plants have shown their potential for developing safe and effective therapies. Particularly, Echinacea purpurea extracts have demonstrated strong anti-inflammatory properties. Therefore, dichloromethanolic extracts of E. purpurea roots (DE-R), rich in alkylamides, were used to produce an anti-inflammatory formulation. To increase therapeutic efficacy, DE-R were loaded into liposomes (LPs), which were also engineered to actively target M1 macrophages via surface functionalization with folic acid (FLPs). The developed formulations were homogeneous, with a mean particle size of ≈114 nm. The liposomes were cytocompatible at all tested concentrations and strongly reduced IL-6 production in LPS-stimulated macrophages. As expected, FLPs + DE-R were 6.3 times better than LPs + DE-R, and 9.7 times greater than free DE-R. The anti-inflammatory activity of free DE-R and DE-R-loaded FLPs was assessed in an experimental rat model of inflammation. A single intra-articular injection of the FLPs + DE-R promoted a significant reduction of edema, inflammatory pain, and immune cell infiltration, particularly of CD68 + macrophages, as well as IL-6 expression. This formulation reduced synovial inflammation more efficiently than free DE-R. We also demonstrated that the developed formulation was safe, as no welfare changes or harmful toxicity to major organs were observed. Therefore, E. purpurea roots extracts loaded in liposomes can be used as a natural, innovative, and powerful new formulation to treat chronic inflammatory diseases. Graphical Abstract

Evaluating the efficacy of topical application of Genista tridentata (L.) (Fabaceae) leaf extract on wound healing in experimental diabetes - Inês Martins Laranjeira; Beatriz Gonçalves; Diana Rodrigues-Fonseca; Alberto C. P. Dias; Filipa Pinto-Ribeiro (Phytochemistry Letters, 2025)

Comparative neurotoxicity of dietary methylmercury and waterborne inorganic mercury in fish: Evidence of optic tectum vulnerability through morphometric and histopathological assessments - Patrícia S. Carvalho; Diana Fonseca-Rodrigues; Mário Pacheco; Armando Almeida; Filipa Pinto-Ribeiro; Patrícia Pereira (Aquatic Toxicology, 2023)

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

Fifteen years of a nationwide culture collection of Neisseria gonorrhoeae antimicrobial resistance in Portugal - Miguel Pinto; João Carlos Rodrigues; Rui Matias; Ivone Água-Doce; Dora Cordeiro; Cristina Correia; João Paulo Gomes; Maria José Borrego; Filipa Alegria; Ana Jacinta Piedade; Maria Beatriz Tomaz; Cristina Toscano; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)